Susan Glaspell’s "Trifles": A Suggested Lesson Plan - Dohal, Gassim (Technium Social Sciences Journal, 2020)
While teaching, a plan will enable a teacher to present his lesson in a smooth way. Being familiar with the text you intend to teach is not enough. As an experienced teacher, I introduce this plan as a model that might be adopted and modified according to the surrounding circumstances a teacher may find her/himself in. A lot of things may interfere in and cause some changes such as time limit, number of students, their level, etc. Hence, instead of leaving all things for luck and chances, I propose this lesson plan, hoping that colleagues and readers ponder it and consider using it.